Patterns of sound change in Deori and Dimasa - Longmailai, Monali; Saikia, Jonali (Nepalese Linguistics, 2019)
This paper compares the two cognate Tibeto- Burman languages, Deori and Dimasa, in terms of sound change patterns in certain class of lexical items. In this regard, it discusses the noun categorization devices besides the counting system, some morphological features and the use of borrowing present in these languages. The paper, thereby, studies briefly their sociolinguistic context of language loss and retention.